Solving fractional differential equations using the Gamma function - Shamuratov Damir (Лучшие интеллектуальные исследования, 2024)
Fractional integration and differentiation is a rapidly developing area of ​​modern analysis, which has a long history and rich content, due to penetration and relationships with various issues of the theory of functions, integral and differential equations, functional analysis, special functions and integral transformations.